PENGGUNAAN INFORMASI AKUNTANSI DALAM KOMPARASI METODE PREDICTOR FINANCIAL DISTRESS INDUSTRI PERTAMBANGAN BATUBARA - NISA, KHOIRUN (Jurnal Akuntansi AKUNESA, 2014)
This study investigate accounting information as predictor of financial distress. Its was conducted to determine the ability of the model Altman, Sprigate, Ohslon and Zmijewski in predicting bankruptcy of industrial coal mining company in Indonesia. Based on a purposive sampling technique, there were fifteen companies of coal mining industry that made the object of research for the period 2011-2013. The analytical method was a binary logistic regression. The results that Springate model had ability predictor of bankruptcy in coal mining in Indonesia.   Keyword : financial distress, bankcuptcy, coal mining industry